Freshening of Antarctic Bottom Water Off Cape Darnley, East Antarctica. Issue 8 (3rd August 2020) - Aoki, S.; Katsumata, K.; Hamaguchi, M.; Noda, A.; Kitade, Y.; Shimada, K.; Hirano, D.; Simizu, D.; Aoyama, Y.; Doi, K.; Nogi, Y.
Abstract: Recently, a source of Antarctic Bottom Water (AABW) was identified off Cape Darnley at the eastern end of the Weddell‐Enderby Basin. However, the behavior and long‐term variability of Cape Darnley Bottom Water (CDBW) are not clearly understood. Hydrographic observations from 1974 to 2016 were compared, and a decade‐long bottom temperature record was analyzed to clarify multidecadal changes in the CDBW in this region and its downstream influences. In the Cooperation Sea, CDBW spread northwestward with its deepest part reaching to approximately 4, 900 dbar. CDBW freshening of 0.001–0.003 decade −1 was revealed. In the Cosmonaut Sea, long‐term AABW warming of approximately 0.01–0.03°C decade −1 was prominent in the deep basin, while freshening was detected on the upper continental slope. Spatial patterns suggest that an interbasin deep transport of excess freshwater is carried by CDBW and fed into the Weddell Gyre, which might act as an abyssal freshwater buffer. Plain Language Summary: Global oceans' abyss is filled with the cold, dense water fed from the Antarctic coastal margin. The Weddell Sea is the most voluminous supplier of this bottom water. In addition to the well‐known source of the bottom water, new source regions are discovered recently: Continental shelf off Cape Darnley, East Antarctica, is one of such regions. Vast parts of the ocean around Antarctica is experiencing freshening for these decades, possibly related to an accelerating ice mass discharge from the Antarctic continent. In contrast, the abyssal Weddell Sea has been known to be warming significantly, acting like a huge heat buffer. Our study shows the newly discovered bottom water off Cape Darnley is carrying an increasing amount of freshwater and feeding the excess freshwater into the abyssal Weddell Sea. This suggests that the Weddell Sea experiences changes that originate from a distant, continental source. Key Points: Long‐term freshening of Antarctic Bottom Water was detected off Cape Darnley, East Antarctica, from the 1970s to 2016 To the west warming was detected near the bottom of the northern basin, while freshening was prominent on the continental slope The freshening signal spread along the upper continental slope, which may feed excess freshwater into the abyssal Weddell Gyre